Industri Olahraga Kota Pontianak Ditinjau Dari Penyewaan Lapangan Futsal - Yuni Artika Putri; Uray Gustian; Rubiyatno Rubiyatno (Journal on Education, 2024)
The sports industry is a business activity carried out by providing a place to exercise specifically providing a futsal field that will be rented out by people who are interested in futsal sports, the purpose of this study was conducted to determine the sports industry in futsal field rental in Pontianak city. This study uses a survey method, quantitative research. The sample amounted to 24 futsal courts. The data collection techniques used are interview techniques and observation sheets. The research data was analyzed using excel which is presented in the form of diagrams and tables. Based on the results of the calculations obtained as follows. The results show that the rental of futsal fields seen from the highest number of members, namely the D'jau futsal field 76 members, and the lowest member of the Arena futsal Sbn field 1 member, from an average of 33 members, the most expensive rental price is Puncak Futsal Field IDR.135,000. The cheapest Borneo One Stadium field is IDR 30,000, from an average rental price of IDR 89,000. Field rentals are more on weekends, namely Saturday totaling 21 tenants, and on weekends tenants tend to be less, namely on Thursdays with a total of 10 tenants. These results show that the sports industry helps in renting futsal fields